Desenvolvimento e estabilidade do néctar de goiaba adoçado com mel de abelha - Moreira, Priscila Ximenes (2010)
The beverage market to tropical fruit and ready to drink has been rising steadily, this growth is associated with practicality and the pursuit of health and fitness. Today, innovations in the development of food and drinks are increasingly looking to associate pleasant taste with functional claims, offering consumers healthier products. This dissertation aimed to develop a guava nectar sweetened with honey, heat-processed hot-fill and study its physical and chemical stability, sensory and microbiological during 120 days of storage at room temperature 28 ± 2 ° C, in bottles of high density polyethylene (HDPE) and compared with a standard sample sweetened with sugar. Product development were evaluated by sensory tests of color, aroma, flavor, overall acceptability, sweetness four formulations (A, B, C and D) with different amounts of guava pulp (35 and 40%) associated with different quantities of honey in soluble solids (10 and 12 ° Brix). Among the formulations tested, the most accepted by consumers was the formulation "C" with 40% of pulp and 10 ° Brix and the same was processed and evaluated after processing every 30 days until the end of the storage period. The results of stability study showed that the product was good acceptance in all attributes evaluated were within the microbiological standards in accordance with the laws and amendments physicochemical not spoiling the product during storage. So this is a viable alternative with good acceptability to the market of drinks ready for consumption.